Produção e transporte do camarão-rosa Farfantepenaeus brasiliensis para a pesca amadora: uma alternativa sustentável? - Vaz, Luciano Jensen (Universidade Federal de São Carlos, 2012)
As well as being popular and growing worldwide, sport fisheries are considered an important recreational, economic and social activity that propels a wide production chain and generates employment and income. The major species of marine shrimp used as live bait in the Brazilian coast used as live bait in sport fishing are: white shrimp Litopenaeus schmitti and pink shrimp Farfantepenaeus brasiliensis and Farfantepenaeus paulensis, all of them included in the list of overexploited species. Although the shrimp are caught in estuaries throughout the year, the main period of capture occurs in the summer months. This fact produces significant fluctuations in the catch throughout the year, occurring in situations that greatly reduced catches. In view of these facts, the cultivation of shrimps for bait production could become an important tool for conservation and regulation of the market for live bait. Thus, the studies that comprise this thesis were directed to the production of pink shrimp F. brasiliensis in biofloc system and management studies related to transportation of shrimp as live bait. From the results observed in thesis, it was observed that there is already a well established method for the production of post-larvae of F. brasiliensis this phase is not an obstacle for the production of live bait. Furthermore, the results show that F. brasiliensis has a potential for the cultivation in biofloc system and can be reared in a stocking density of up to 100 shrimp/m² during the nursery stage and in a density of up to 75 shrimp/m² during the grow-out phase. Finally, it was observed that for the transport of F. brasiliensis the water temperature should be between 16 and 19 °C and stocking density should not exceed 3 shrimp / L or (16.5 g / L), the transport is recommended for a maximum of 10 hours to prevent mortality. Therefore, according to all data obtained in this thesis, post-larvae production, cultivation in biofloc system and transportation of F. brasiliensis to be used as live bait proved to be technically viable solutions to meet the needs of sport fisheries.
Keywords: Aquicultura; Carcinocultura; Pesca com isca viva; Farfantepenaeus brasiliensis; Bioflocos; Crescimento; Sobrevivência; Densidade de estocagem; Live bait; Biofloc; Grow-out; Survival; Stocking density; CIENCIAS BIOLOGICAS::ECOLOGIA